A partially sex‐reversed giant kelp sheds light into the mechanisms of sexual differentiation in a UV sexual system. Issue 1 (29th July 2021) - Müller, Dieter G.; Gaschet, Enora; Godfroy, Olivier; Gueno, Josselin; Cossard, Guillaume; Kunert, Maritta; Peters, Akira F.; Westermeier, Renato; Boland, Wilhelm; Cock, J. Mark; Lipinska, Agnieszka P.; Coelho, Susana M.
Summary: In UV sexual systems, sex is determined during the haploid phase of the life cycle and males have a V chromosome whereas females have a U chromosome. Previous work in the brown alga Ectocarpus revealed that the V chromosome has a dominant role in male sex determination and suggested that the female developmental programme may occur by 'default'. Here, we describe the identification of a genetically male giant kelp strain presenting phenotypic features typical of a female, despite lacking the U‐specific region. The conversion to the female developmental programme is however incomplete, because gametes of this feminized male are unable to produce the sperm‐attracting pheromone lamoxirene. We identify the transcriptomic patterns underlying the male and female specific developmental programmes, and show that the phenotypic feminization is associated with both feminization and de‐masculinization of gene expression patterns. Importantly, the feminization phenotype was associated with dramatic downregulation of two V‐specific genes including a candidate male‐determining gene. Our results reveal the transcriptional changes associated with sexual differentiation in a UV system, and contribute to disentangling the role of sex‐linked and autosomal gene expression in the initiation of sex‐specific developmental programmes. Overall, the data presented here imply that the U‐specific region is not required to initiate the female developmental programme, but is critical to produce fully functional eggs, arguing against the idea that female is the 'default' sex in this species.